Continous seismic raw data (Ocean Bottom Seismometer working area dataset) of RV POSEIDON during cruise POS515, Poseidon mud volcano chain, Calabrian Arc, Mediterranean Sea - Michael Riedel; Cord Papenberg; Jörg Bialas (PANGAEA, 2024)
The data comprise continuous records of seismic raw data acquired with ocean bottom seismometers (OBS). The data were collected at Poseidon mud volcano chain during expedition POS515 with the research vessel POSEIDON (Riedel et al., 2017) in the Mediterranean Sea, Calabrian Arc offshore southern Italy (map under further details). The entire data set consists of 12 OBS stations. Each OBS consist of 4 channels (channel 1: hydrophone; channel 2: horizontal component 1; channel 3: horizontal component 2; channel 4: vertical component). Data are not corrected for clock-drift. Data format is Passcal-SEGY. Data are accessible using the seismological software tools provided by EarthScope: https://www.passcal.nmt.edu/content/software-resources. The data were recorded using: HTI-04_PCA_ULF hydrophones from High Tech Inc., Short-period 4.5 Hz geophones and Three-component seismometers (K/MT-210 manufactured by KUM GmbH). The recording device is an MBS recorder of SEND GmbH